PERENCANAAN STRUKTUR ATAS GEDUNG KANTOR CV. GRAHA SUNGKAI TANGAH JUA BUKITTINGGI - Bintang Friz Hardatama; Surya Eka Priana; Febrimen Herista (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Planning of the upper structure the office building CV. Graha Sungkai aims to improve infrastructure facilities according to office building in general. This plan is planning the construction of the building structure to achieve a strong, safe, and fulfill the requirements set out in the regulations that apply to the planning of the building structure. Upper Structure Planning Office Building CV. Graha Sungkai preliminary Design using ETABS. Loads that are input into the ETABS are dead load, live load, building weight, earthquake load. From the preliminary design results, it was found that the main beam reinforcement (BI 1) is 40 × 50 in size with a concrete quality of 30 Mpa, steel quality 420 Mpa, reinforcement for the upper support 5D16, the lower support 3D16, the upper field reinforcement 3D16, the lower field 3D16, the support stirrup reinforcement 10 – 150, field stirrups 10 – 200. Column 1 size 60 × 60 concrete quality 30 Mpa, Steel Quality 420 Mpa total axial reinforcement 16 D 22, shear reinforcement 10 – 200. Reinforcement roof slab 10 – 200, pitch 10 - 300. Reinforcement floor slab 10 – 100, pitch 10 – 250. From the planning above, it can be concluded that it has fulfilled the terms and conditions contained in the Indonesian regulations and standards.Key word: Beams, Columns, Floor slabs, Roof Slabs, Loads, Reinforcements